FAKTOR PENYEBAB KEJENUHAN BELAJAR SEJARAH KEBUDAYAAN ISLAM (SKI) PADA SISWA KELAS XI JURUSAN KEAGAMAAN DI MAN TEMPEL SLEMAN - Nimatul Fauziyah (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2013)
The background of this research is the emergence of learning constraints experienced by students in the Department of Religious MAN Tempel Sleman. The problem of this study is how students who experience saturation during SKI learning process and what factors are causing the saturation in learning SKI.This qualitatif research resulted several findings, namely: 1) the attitudes of the bored students during SKI class were lying, telling himself, not paying attention, making noisy or teasing other friends, playing HP, being late to come to the class after the break and asking permission to leave the classroom. 2) Factors causing saturation among students of religius program class XI during SKI class included: 1) a unpleasant learning atmosphere, 2) fatigue of writing too much summary, 3) fatigue due to staying up late, 4) the saturation caused by monotonous teaching methods, 5) inadequacy of reference books for students of class XI SKI Religious Department, 6) the monotonous learning tasks, and 7) less teacher’s attention to students’ motivation.